The diversity of the Genus Panulirus trafficked through the Fish Quarantine Station Controlling the Quality and Safety of Fishery Products, Aceh Province - Lastria, Lusi; Darmarini, Ananingtyas S; Aly, Muhammad; Heriansyah; Wardiatno, Yusli (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The genus Panulirus is one of the important fishery commodities for Aceh Province. In the context of the sustainability of these resources, it is necessary to apply regulations properly. The purpose of the apprenticeship activity is to determine the type, number and origin of the lobster catching area that is trafficked through the Fish Quarantine Station for Quality Control and Safety of Fishery Products in Aceh. The activity is carried out from February to April 2022. The method used is by observing activities, and collecting data on the types of lobsters that are trafficked. There are 6 types of lobster that are trafficked at the Fish Quarantine Station for Quality Control and Safety of Fishery Products in Aceh, including; Panulirus homarus, Panulirus ornatus, Panulirus penicillatus, Panulirus polyphagus, Panulirus longipes and Panulirus versicolor. Every month the quarantine stations carry out inspections before shipping an average of 1929 individuals per month. The type of Panulirus versicolor is the type with the highest percentage (34%) sent through. The origin of lobster catching consists of 8 areas, namely Banyak Island (Aceh Singkil), Simeulue Island, Labuan Haji (South Aceh), Meulaboh (West Aceh), Calang and Lamno (Aceh Jaya), Banda Aceh and Sabang Island.